1992
DOI: 10.1042/bj2860065
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of hormonal regulation of glutathione transferase in rat liver and adrenal glands. Sex differences and demonstration that growth hormone regulates the hepatic levels

Abstract: Immunoblot experiments and reverse-phase h.p.l.c. were used to study the levels of glutathione transferase subunits 1, 2, 3, 4, 6, 7 and 8 in the liver and adrenal of intact and hypophysectomized male and female Sprague-Dawley rats. A sexual dimorphism in the levels of several of these isoenzymes and in their responses to hypophysectomy was demonstrated. In the liver of sham-operated females and males there are differences in glutathione transferase activities and isoenzyme pattern. H.p.l.c. analysis showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
5
26
3
Order By: Relevance
“…GH responsiveness is demonstrated here for the first time for phytanoyl-CoA dioxygenase, cysteine sulfinic acid decarboxylase, glutaryl-CoA dehydrogenase, peptidylprolyl isomerase, hnRNP K, hnRNP D-like, hnRNP A3, NF45, betaine homocysteine S-methyltransferase, and CMP-N-acetylneuraminic acid synthetase. Interestingly, GH has been shown to regulate the expression of alcohol sulfotransferase at the level of gene expression (12,48) and the expression of GSTs Yb1 and Yb2 at the gene and protein level (11,44). In the present study, however, these proteins did not display changes in nuclear intensity in response to GH treatment.…”
Section: Figcontrasting
confidence: 54%
See 1 more Smart Citation
“…GH responsiveness is demonstrated here for the first time for phytanoyl-CoA dioxygenase, cysteine sulfinic acid decarboxylase, glutaryl-CoA dehydrogenase, peptidylprolyl isomerase, hnRNP K, hnRNP D-like, hnRNP A3, NF45, betaine homocysteine S-methyltransferase, and CMP-N-acetylneuraminic acid synthetase. Interestingly, GH has been shown to regulate the expression of alcohol sulfotransferase at the level of gene expression (12,48) and the expression of GSTs Yb1 and Yb2 at the gene and protein level (11,44). In the present study, however, these proteins did not display changes in nuclear intensity in response to GH treatment.…”
Section: Figcontrasting
confidence: 54%
“…Sexually dimorphic hepatic expression at the mRNA or/and protein level has been demonstrated previously for several of these proteins. These include the male-predominant proteins Nhydroxyarylamine sulfotransferase (12,41), hydroxyacid oxidase 3 (12), cysteine sulfinic acid decarboxylase (42), regucalcin (43), GSTs Yb1 and Yb2 (11,44), and various estrogen sulfotransferases (12,45), and the female-predominant alcohol sulfotransferases (12, 46 -48). The sexually dimorphic pattern of expression of the other proteins identified in this study and listed in Table III is reported here for the first time.…”
Section: Figmentioning
confidence: 99%
“…In particular, gender differences in GH secretion patterns are involved in the regulation of GSTs in vivo (Staffas et al 1992). Continuous administration of GH yields a female isoenzyme pattern, whereas discontinuous administration of GH yields a male pattern (Staffas et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several enhancer elements, including the xenobiotic-responsive element (XRE), the antioxidantresponsive element (ARE), the glucocorticoid-responsive element (GRE) and the barbiturate-responsive element (Barbie box) have been identified in the 5 -flanking regulatory region of this gene and are responsible for its induction by polycyclic aromatic hydrocarbons including 3-methylcholanthrene and -naphtoflavone, products of oxidative stress, dexamethasone and phenobarbital respectively (Rushmore et al 1991, Hayes & Pulford 1995. With respect to the endogenous regulation of GST expression, it is known that adrenocorticotrophic (Mankowitz et al 1990), growth (Staffas et al 1992), thyroid (Kelley & Bjeldanes 1995, Beckett et al 1988) and steroid hormones (Hatayama et al 1986) are involved. At the regulatory level, it has been shown that insulin induces the transcription of the human GSTP1 gene via one of the SP-1 sites (GC/box) in the 5 -flanking regulatory region, whilst retinoic acid suppresses hGSTP1 expression through the AP-1 site (Xia et al 1993(Xia et al , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The level of GST expression represents an important factor in determining the sensitivity of organisms to endogenous and exogenous compounds and has been shown to decline with aging (Cho et al 2003;Richie et al 1992). Moreover, GH has been shown to regulate the level of cytosolic GSTs in certain target organs (Coecke et al 2000;Srivastava and Waxman 1993;Staffas et al 1992). In our study, although no differences of the M class GSTs in mitochondria were observed, cytosolic GSTM4 was higher in WT mice and increased in IGF-1-treated GHRKO mice.…”
Section: Discussionmentioning
confidence: 99%